Istinbath Hukum Untuk Meningkatkan Kesadaran Masyarakat Akan Pencatatan Nikah - Jauhari, Jauhari; Candra, Andi; Afriani, Kinaria (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Islamic law does not recognize special marriage registration. In Islamic law, marriage registration is not referred to as one of the elements or conditions of marriage. In the days of the Prophet Muhammad SAW, there were no terms for recording marriages. An eligible marriage and a marriage ceremony are considered legitimate. This research uses a library method, which means that this research looks at the theories, concepts, and provisions of Islamic sharia'at related to the problem being studied. The istinbath qiyas method associates marriage recording with verse 282 of Surah al-Baqarah, which states that when a person makes a transaction, they must write it down. It's because with this record, people can avoid problems that may occur in the future if a denial occurs.